Treatment and Outcome Analysis of 639 Relapsed Non-Hodgkin Lymphomas in Children and Adolescents and Resulting Treatment Recommendations - Burkhardt, Birgit; Taj, Mary; Garnier, Nathalie; Minard-Colin, Veronique; Hazar, Volkan; Mellgren, Karin; Osumi, Tomoo; Fedorova, Alina; Myakova, Natalia; Verdu-Amoros, Jaime; Andres, Mara; Kabickova, Edita; et al. (Cancers, 2021)
Despite poor survival, controversies remain in the treatment for refractory or relapsed pediatric non-Hodgkin lymphoma (r/r NHL). The current project aimed to collect international experience on the re-induction treatment of r/r NHL, hematopoietic stem cell transplantation (HSCT), risk factors associated with outcome, and to suggest treatment recommendations. Inclusion criteria were (i) refractory disease, disease progression or relapse of any NHL subtype except anaplastic large cell lymphoma, (ii) age < 18 years at initial diagnosis, (iii) diagnosis in/after January 2000. Data from 639 eligible patients were evaluable. The eight-year probability of overall survival was 34 ± 2% with highly significant differences according to NHL subtypes: 28 ± 3% for 254 Burkitt lymphoma/leukemia, 50 ± 6% for 98 diffuse large B-cell lymphomas, 57 ± 8% for 41 primary mediastinal large B-cell lymphomas, 27 ± 3% for 177 T-lymphoblastic lymphomas, 52 ± 10% for 34 precursor-B-cell lymphoblastic lymphomas and 30 ± 9% for 35 patients with rare NHL subtypes. Subtype-specific factors associated with survival and treatment recommendations are suggested. There were no survivors without HSCT, except in few very small subgroups. Conclusions: There is an urgent need to further improve survival in r/r NHL. The current study provides the largest real-world series, which underlines the role of HSCT and suggests treatment recommendations.
Keywords: stem cell transplant; refractory and relapsed non-Hodgkin lymphoma; children and adolescents